Immediate Treatment Outcome of Convulsive Status Epilepticus Following a Specific Management Protocol (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Status epilepticus (SE) is a medical and neurologic emergency. Rapid and aggressive treatmentis required to prevent neuronal damage, systemic complications and death. Standardized treatment guidelines may improve the quality of emergency managementof SE.Objectives: The objective of the present study was to assess under lying causes of seizure and the immediate outcome of treatment following the specific proposed management protocol care.Methodology: This cross-sectional study was undertaken on 94 consecutive cases admitted inPediatrics department of Dhaka Medical College Hospital, Dhaka diagnosed as convulsive status epilepticus, age